Xenotransplantation of Genetically Modified Neonatal Pig Islets Cures Diabetes in Baboons - Hawthorne, Wayne J.; Salvaris, Evelyn J.; Chew, Yi Vee; Burns, Heather; Hawkes, Joanne; Barlow, Helen; Hu, Min; Lew, Andrew M.; Nottle, Mark B.; O’Connell, Philip J.; Cowan, Peter J. (Frontiers in Immunology, 2022)
Xenotransplantation using porcine donors is rapidly approaching clinical applicability as an alternative therapy for treatment of many end-stage diseases including type 1 diabetes. Porcine neonatal islet cell clusters (NICC) have normalised blood sugar levels for relatively short periods in the preclinical diabetic rhesus model but have met with limited success in the stringent baboon model. Here we report that NICC from genetically modified (GM) pigs deleted for αGal and expressing the human complement regulators CD55 and CD59 can cure diabetes long-term in immunosuppressed baboons, with maximum graft survival exceeding 22 months. Five diabetic baboons were transplanted intraportally with 9,673 – 56,913 islet equivalents (IEQ) per kg recipient weight. Immunosuppression consisted of T cell depletion with an anti-CD2 mAb, tacrolimus for the first 4 months, and maintenance with belatacept and anti-CD154; no anti-inflammatory treatment or cytomegalovirus (CMV) prophylaxis/treatment was given. This protocol was well tolerated, with all recipients maintaining or gaining weight. Recipients became insulin-independent at a mean of 87 ± 43 days post-transplant and remained insulin-independent for 397 ± 174 days. Maximum graft survival was 675 days. Liver biopsies showed functional islets staining for all islet endocrine components, with no evidence of the inflammatory blood-mediated inflammatory reaction (IBMIR) and minimal leukocytic infiltration. The costimulation blockade-based immunosuppressive protocol prevented an anti-pig antibody response in all recipients. In conclusion, we demonstrate that genetic modification of the donor pig enables attenuation of early islet xenograft injury, and in conjunction with judicious immunosuppression provides excellent long-term function and graft survival in the diabetic baboon model.